A centimeter scale self-standing two-dimensional ultra-thin mesoporous platinum nanosheet. Issue 2 (3rd October 2019) - Li, Yunqi; Liu, Yuwei; Li, Jing; Xiong, Danping; Chen, Xiran; Liu, Mingtao; Zhong, Zheng; Malgras, Victor; Bando, Yoshio; Yamauchi, Yusuke; Xu, Jun
Abstract : A kind of mesoporous 2D Pt nanosheets with unique structural features exhibits a high electrocatalytic activity towards the oxygen reduction reaction (ORR). Abstract : Here, we report the unprecedented synthesis of centimeter scale self-standing mesoporous Pt nanosheets. Due to solvent evaporation, spherical micelles made of poly(styrene- b -2-vinyl pyridine- b -ethylene oxide) (PS-P2VP-PEO) self-assemble in a well-ordered fashion, over the entire surface of the substrate, and confined within an ultra-thin layer. Metal deposition around the micelles is carried out through a two-step reduction process using two different reducing agents. After removing the micelles and substrate, a continuous self-standing ultra-thin mesoporous Pt nanosheet can be obtained (∼15 nm thick). Due to several unique porous structural features, including abundant active sites, high surface area, and long-range orthogonally ordered pores, the obtained material is expected to deliver high performance in a wide range of electrochemical applications. This novel synthetic strategy opens a new route to design and control novel 2D mesoporous metal nanosheets with various functions.